CRYPTOCURRENCY AS A PHENOMENON IN THE MODERN ECONOMY - Tretyakova S.; Khairullina I.; Akhmetshin B. R. (Uzbekistan Open Conference, 2025)
The article considers cryptocurrency not as an "Internet coin", but as a combination of technologies, market practices and institutions that change the ways of issuing, circulation and accounting of value. The material is devoted to three topics: demand factor - institutionalization through exchange-traded funds and use in cross-border settlements, main risks - price volatility, operational disruptions, and external environmental impacts, regulatory responses - the EU MiCA system, and the Central Bank's interest in digital currencies.
Keywords: cryptocurrency; blockchain; stable coins; Bitcoin; MiCA; ETF; tokenization; CBDC